Sri Lanka : Recent Economic and Policy Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper reviews economic and policy developments in Sri Lanka during 1996-98. Despite the slowdown in world trade and economic growth, Sri Lanka's economy grew in 1998 at close to its historic average rate. The recorded 4 3/4 percent growth in real GDP was lower than 1997 when the economy was recovering after a bad harvest. In the first twelve months following the outbreak of the Southeast Asian crisis, Sri Lanka was helped by reduced export competition and lower commodity prices. But by the middle of 1998, growth in Sri Lanka started to slow markedly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet